ANTIBACTERIAL TESTED STAPHYLOCOCCUS AUREUS FROM ETHANOL EXTRACT OF NONI FRUIT - anggraeni, Ratih (Jurnal FARMASIMED (JFM), 2023)
The various types of plants that Indonesia has should be protected and maintained in diversity. Many types of plants are used as medicinal plants. Some taste sweet, astringent, sour, and even bitter. One of them is the noni plant. The noni plant has fruit that tastes bitter and gives off an unpleasant odor. However, noni fruit contains antibacterial properties. More than one bacteria is found in the human body. One of them is Staphylococcus aureus which can infect if the immune system is low. The main treatment for bacterial infections uses antibiotics. Frequent use of antibiotics can cause resistance. To overcome this resistance, research was carried out on ethanol extract of noni fruit which is expected to inhibit the growth of these bacteria. This research is experimental using Staphylococcus aureus bacteria as a bacterial test using the disc diffusion method. The antibiotic amoxicillin was used as a positive control. The diameter of the inhibition zone will determine the antibacterial activity of the bacterial medium. The ethanol extract of noni fruit that was tested provided evidence that it could prolong the growth of Staphylococcus aureus bacteria. The concentration of the test solution is divided into 3, namely 25%, 50% and 75%. The diameters of the inhibition zones are 15.67 mm, 19.7 mm, and 23.97 mm, respectively. Differences in the concentration of the test solution can affect the diameter of the inhibition zone in the bacterial medium. The test solution with a concentration of 75% had the best antibacterial inhibition power, namely 23.97 mm. Keywords: noni fruit, Staphyococcus aureus, antibacterial